Improving approaches to the development of personnel management in Russia based on international experience - A. O. Azarova; M. K. Buylova (Вестник университета)
The article examines HR trends that have been successfully implemented in foreign countries and Russia in the last few years. Approaches to HR management during the pandemic coronavirus 2020–2021 have been reviewed. Based on an analysis of statistical data, nine most successful trends in HR management have been identified and examined in detail, their key factors were described, a comparison of their application in Russia and worldwide was made, and barriers to mass implementation have been noted.